Synthesis, Characterization, and Application of Fe2O3 Nanophotocatalyst for the Treatment of Various Pollutants in Aqueous Phase: A Systematic Review - Aya Khalaf; Duaa Abu-Dalo; Ehab AlShamaileh (The Scientific World Journal)
Many techniques are used for the treatment of wastewater, including physical, chemical, biological, physiochemical, and biophysical methods. Advanced oxidation processes (AOPs), a chemical approach, are a key procedure for wastewater treatment. AOPs are applied to nonbiodegradable effluents, using less energy and chemicals while producing a completely biodegradable intermediate sample that can then undergo additional treatment to completely remove all organic matter. The AOPs can be chemical, photochemical, sonochemical, or electrochemical. Photochemical reactions accelerate the breaking down of organic pollutants using a photocatalyst that absorbs light and serves as a catalyst for chemical operations. There are a lot of photocatalysts that are used in water purification, such as TiO2, ZnO, ZrO2, CdS, CeO2, ZnS, FeO, Fe2O3, SnO2, and WO3, and most of them are at the nanoscale. This article analyzes and covers the main aspects of using Fe2O3 nanoparticles for the purification of water and wastewater. It covers the application of Fe2O3 nanoparticles in the treatment of water and wastewater and the mechanisms of solar photodegradation of iron oxide (Fe2O3) photocatalysts. It shows the Fe2O3 nanoparticle synthesis methods and introduces the advantages and disadvantages of each technique. The review makes comparisons between the photocatalytic membrane reactor and the suspended system, as well as upcoming challenges and opportunities related to using Fe2O3 nanoparticles in these processes. This provides researchers with a different perspective on the photocatalysis outcomes that might be attained when the Fe2O3 photocatalysts are incorporated into various treatment systems.